Metastatic cutaneous squamous cell carcinoma of the parotid gland: prognostic factors. Issue 3 (5th July 2017) - Coombs, A C; Butler, A; Allison, R
Abstract: Background: Metastatic cutaneous squamous cell carcinoma is the most common parotid malignancy in Australasia. Prognostic indicators are not clearly defined and the extent of surgical resection required is controversial. Methods: A retrospective analysis was conducted of 63 patients who underwent surgery for metastatic cutaneous squamous cell carcinoma of the parotid gland at a tertiary hospital over a 10-year period. Results: The five-year overall survival rate was 53 per cent, the disease-specific survival rate was 78 per cent and the locoregional control rate was 72 per cent. Immunosuppression and no adjuvant radiotherapy were associated with a significant reduction in disease-specific survival. None of the factors analysed had a significant effect on locoregional control rates. Conclusion: More extensive surgery, including lateral temporal bone resection, may improve local control rates in cases of more advanced disease. The reduced survival of immunocompromised patients must be considered when planning their management.